2020
DOI: 10.3390/w12020503
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Ecological Footprint Method for Water Resources Utilization Assessment in the Cities

Abstract: Economic development and increasing population density along the lower reaches of the Yellow river have challenged the river’s ability to meet human and ecological demand. The evaluation of the sustainability of water resources in the lower reaches of the Yellow River is of great significance for the achievement of high-quality development in the region. Based on an improved ecological footprint method considering soil water, the spatial and temporal evolution of the water resources ecological footprint and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The water resources ecological footprint (i.e., water volume ecological footprint) refers to water resource consumption by human beings for production and life (Wang and Liu 2019), and the total water resource ecological footprint in the region was selected as the water resource input, excluding the water quality ecological footprint. The water resource ecological footprint in the region was calculated by using the research method of Li et al (2020). Due to space limitations, the detailed calculation method is not repeated here.…”
Section: Input and Output Variablementioning
confidence: 99%
“…The water resources ecological footprint (i.e., water volume ecological footprint) refers to water resource consumption by human beings for production and life (Wang and Liu 2019), and the total water resource ecological footprint in the region was selected as the water resource input, excluding the water quality ecological footprint. The water resource ecological footprint in the region was calculated by using the research method of Li et al (2020). Due to space limitations, the detailed calculation method is not repeated here.…”
Section: Input and Output Variablementioning
confidence: 99%
“…For instance, Wang et al calculated the per capita WEF and WECC and analyzed the water resources ecological pressure index to assess the sustainable utilization level of water resources in Hubei, China [25]. Li et al comprehensively evaluated the utilization of water resources and the spatial and temporal evolution of WEF and WECC in the lower Yellow River [26]. Su et al calculated WEF and WECC of four urban areas in China and suggested that adjusting industrial structure and repairing the inequality of water resources can promote the sustainable development of social economy [27].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we took the Wuhan Metropolitan Area, a typical metropolitan area in central China, as the research object to achieve the following research aims: (1) construct a three-dimensional WEF model; (2) construct an evaluation index system for the regional sustainable utilization level of water resources based on the model; (3) analyze the factors influencing the change in WEF using the LMDI. This research would help to improve and supplement the theoretical system of sustainable water resources development by constructing a three-dimensional WEF model and introducing two indicators of NCF and NCS [25][26][27]. In addition, we provide references for government policies and plans in the metropolitan area development, water resources allocation and dispatching and industrial structure adjustment by analyzing the contribution of WEF intensity, economic development, population pressure and WECC to the change in WEF based on LMDI.…”
Section: Introductionmentioning
confidence: 99%
“…Also, other environmental footprint methodologies (Vanham et al, 2019) try to find a way to involve the water issues into their own methodology (Li et al, 2020;Wang et al, 2020). Currently, the water ecological footprint is described in the literature (Hu et al, 2008;Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%